Assessment of automatic air cooling system using DC fan for photovoltaic panel / Amelia binti Abd Razak. - Amelia Abd Razak (School of Electrical System Engineering, Universiti Malaysia Perlis, 2017)
The main goal of this research work is to assess the automatic air cooling system by using DC fan for PV panel applications. There are sub-objectives as the purpose to achieve the research goal ; to investigate the effect of solar irradiance and PV panel temperature on PV panel output performance by using PVsyst software ; to design and develop the automatic air cooling system with the desired number of the DC fan for a unit of PV panel ; to implement and analyse the automatic air cooling system on PV panel under outdoor conditions with considering economic aspect.